The impact of the outsourcing ban in Mexico on labor market outcomes. An analysis using worker level data - Fernando Moreno-Contreras; Edwin van Gameren (Journal for Labour Market Research)
Abstract Mexico’s ban on subcontracting or outsourcing practices, implemented in 2021, represents a pivotal development in the nation’s labor market policies. This paper presents an analysis of the effects of the prohibition of domestic outsourcing, drawing on individual worker-level data. Employing a difference-in-differences approach with multiple time periods and heterogeneous cohort and time effects, we examine the impact of the ban on various aspects of the workforce, including wages, formality rates, and labor rights coverage. Our analysis reveals increases in wages of about 6% for previously outsourced workers, slightly higher for those who maintained their workplace, and up to 10 to 13% when transitioning shortly after the ban’s enactment. Moreover, these workers experienced greater increases in formality rates and labor rights coverage compared to those who had already been hired directly prior to the policy change. We do find some evidence for strategic behavior related to the outsourcing ban’s implementation. These findings shed light on the complex dynamics of labor policy reform in Mexico and have significant implications for the country’s labor landscape.